2013
DOI: 10.1210/en.2013-1272
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Induces Wnt10b in Osteoclasts From Female Mice to Enhance Coupling to Osteoblasts

Abstract: In young adults, bone lost through osteoclast-mediated resorption is precisely replaced in both location and amount. Understanding how these two processes are coupled is crucial to advancing treatments for osteoporosis, a disease that progresses when the processes become uncoupled. We documented that osteoclasts secrete the mammalian integration 1 gene that is the homolog of Drosophila Wngless (Wnt) 10b, bone morphogenetic protein 6 (BMP6), and the chemokine sphingosin 1 phosphate (S1P) to promote mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 31 publications
2
61
0
Order By: Relevance
“…Others found that S1P production via SphK1 in osteoclasts and its secretion stimulates osteoblast migration and survival, which supports bone formation [79,80,81,82]. In a different study, the role of TGF-beta1 on osteoclast-mediated support of mineralization was investigated and revealed that S1P production was, however, not induced in osteoclasts upon TGF-beta1 stimulation [83]. Up-regulation of OPG and osteoblast differentiation markers upon S1P stimulation was another finding which may lead to the inhibition of osteoclast differentiation and promotion of bone formation [84].…”
Section: Function Of S1p In Bloodmentioning
confidence: 99%
“…Others found that S1P production via SphK1 in osteoclasts and its secretion stimulates osteoblast migration and survival, which supports bone formation [79,80,81,82]. In a different study, the role of TGF-beta1 on osteoclast-mediated support of mineralization was investigated and revealed that S1P production was, however, not induced in osteoclasts upon TGF-beta1 stimulation [83]. Up-regulation of OPG and osteoblast differentiation markers upon S1P stimulation was another finding which may lead to the inhibition of osteoclast differentiation and promotion of bone formation [84].…”
Section: Function Of S1p In Bloodmentioning
confidence: 99%
“…TGF-β and IGF-1 are both stored in bone matrix and released by its resorption by OC, with the former acting to promote migration of mesenchymal stem cells to newly resorbed sites (136, 137). TGF-β also induces OC to express CXCL16 and Wnt10b, which induce recruitment and mineralization by osteoblasts, respectively (138, 139). Sphingosine-1-phosphate (140) and collagen triple helix repeat containing 1 (141) have been proposed as possible secreted coupling factors that enhance bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of Wnt7b can be induced by PTH, has been shown to increase with osteoblastic differentiation and to increase bone mass as well as osteoblast number in vivo [29]. Wnt10b is an important factor in coupling the actions of osteoblasts and osteoclasts, while also being able to enhance commitment to the osteoblastic lineage [30, 31]. In contrast, the expression of Wnt5a , reported to antagonize canonical Wnt signaling by stimulating destruction of β-catenin via GSK3β [32], was unaffected by PTH treatment in both WT and KO CM treated groups (Fig.…”
Section: Resultsmentioning
confidence: 99%